Utilising genetically informed research designs to better understand family processes and child development: implications for adoption and foster care focused interventions. (October 2019) - Sellers, Ruth; Smith, Amelia; Leve, Leslie D; Nixon, Elizabeth; Cane, Tam Chipawe; Cassell, Jackie; Harold, Gordon
Understanding the interplay between genetic factors and family environmental processes (e.g. interparental relationship quality, positive vs negative parenting practices) and children's mental health (e.g. anxiety, depression, conduct problems, ADHD) in the contexts of adoption and foster care research and practice is critical for effective prevention and intervention programme development. While evidence highlights the importance of family relationship processes (e.g. interparental relationship quality, parent‒child relationship quality) for the mental health and well-being of children in adoption and foster care, there is relatively limited evidence of effective interventions specifically for these families. Additionally, family-based interventions not specific to the context of adoption and foster care typically show small to medium effects, and even where interventions are efficacious, not all children benefit. One explanation for why interventions may not work well for some is that responses to an intervention may be influenced by an individual's genetic make-up. Alternatively, the targets of family relationship level interventions (e.g. parenting processes) may not always affect the specific environment 'trigger' deemed salient to specific child/adolescent outcomes. This article summarises how genetically informed research designs can help disentangle genetic from environmental processes underlying psychopathology outcomes for children, and how this evidence can provide improved insights into the development of more effective preventive intervention targets for adoptive and foster families. We discuss current difficulties in translating behavioural genetics research to prevention science and provide recommendations to bridge the gap between behavioural genetics research and prevention science, with lessons for adoption and foster care research and practice.